Treatment algorithms for special cases - Emel Bülbül Başkan (Galenos Publishing House, 2022)
Treatment of psoriasis differs in special cases such as in women who wish to become pregnant, during pregnancy and lactation, in pediatric and geriatric populations, in the presence of obesity or chronic viral diseases, and during the COVID-19 pandemic. Due to their well-known teratogenic effect, neither topical nor systemic use of retinoids is recommended in any period of pregnancy and lactation. Literature data on treatment approaches in psoriasis in children is less than in adults, and safety data usually relate to short-term use. There is a multifactorial relationship between psoriasis and obesity; response to treatment is lower in obese patients with a body mass index greater than 30. It should be noted that the elderly have comorbidities and concomitant drug use, which increases the likelihood of side effects and drug interactions of psoriasis medications. In the presence of a viral disease, many agents used in the treatment of psoriasis carry the risk of exacerbating the infection due to their immunosuppressive properties. In such a case, the option that can be considered apart from topical therapies is narrowband phototherapy. It was observed during the COVID-19 pandemic that there had been no increase in the risk of infection-related mortality and morbidity solely due to biological therapy.